Cabinet reshuffles and Parliamentary no-confidence motions - Fleming, TG; González-Bustamante, B; Schleiter, P (Cambridge University Press, 2022)
How do cabinet reshuffles affect the parliamentary opposition’s use of no-confidence motions in the government? Opposition parties employ no-confidence motions as electoral signals to highlight government incompetence, and to position themselves as a government in waiting. We argue that cabinet reshuffles - by which prime ministers respond to policy failures, scandals, poor ministerial performance, and disloyalty - present an opportunity for the opposition to deploy no-confidence motions to this end. The incentives to deploy this strategy, however, are contingent on the nature of the party system and are greatest where party system concentration positions a single opposition party as the alternative to the government and sole beneficiary of a no-confidence vote. We test this expectation using a multilevel modelling approach applied to data on reshuffles in 316 governments and sixteen parliamentary democracies, and find support for our expectation: Cabinet reshuffles raise the probability of no-confidence motions conditional on party system concentration.